Isolation and Characterization of Embryonic Stem Cell-Derived Cardiac Purkinje Cells. (24th March 2015) - Maass, Karen; Shekhar, Akshay; Lu, Jia; Kang, Guoxin; See, Fiona; Kim, Eugene E.; Delgado, Camila; Shen, Steven; Cohen, Lisa; Fishman, Glenn I.
Abstract: The cardiac Purkinje fiber network is composed of highly specialized cardiomyocytes responsible for the synchronous excitation and contraction of the ventricles. Computational modeling, experimental animal studies, and intracardiac electrical recordings from patients with heritable and acquired forms of heart disease suggest that Purkinje cells (PCs) may also serve as critical triggers of life-threatening arrhythmias. Nonetheless, owing to the difficulty in isolating and studying this rare population of cells, the precise role of PC in arrhythmogenesis and the underlying molecular mechanisms responsible for their proarrhythmic behavior are not fully characterized. Conceptually, a stem cell-based model system might facilitate studies of PC-dependent arrhythmia mechanisms and serve as a platform to test novel therapeutics. Here, we describe the generation of murine embryonic stem cells (ESC) harboring pan-cardiomyocyte and PC-specific reporter genes. We demonstrate that the dual reporter gene strategy may be used to identify and isolate the rare ESC-derived PC (ESC-PC) from a mixed population of cardiogenic cells. ESC-PC display transcriptional signatures and functional properties, including action potentials, intracellular calcium cycling, and chronotropic behavior comparable to endogenous PC. Our results suggest that stem-cell derived PC are a feasible new platform for studies of developmental biology, disease pathogenesis, and screening for novel antiarrhythmic therapies. Stem Cells 2015;33:1102–1112